Analisis Koreografi Tari Tanggok - Ningsih, Ayu Sri (PPSDP Undergraduate Journal of Educational Sciences, 2025)
Tanggok dance is a traditional dance in the form of customs in an area where young girls usually go to Ayek Itam to catch fish. Tanggok dance is a dance created by the Ogan Komering Ulu district created by Erma Yanti in 2009, which the author then packaged into a traditional dance with everyday movements that tells the story of the daily lives of teenagers in the area. Daily activities of the people of Sumber Rahayu village who have the habit of fishing when the fishing season arrives using the traditional tanggok tool. The aim is to find out and describe the structure of choreography, clothing, make-up, dance movements and props. The method used in this work is the exploration method. The data that has been collected is then described and analyzed based on the problem formulation and objectives. This location is in Sumber Rahayu village, South Sumatra, Muara Enim while the data source comes from the creator of the Nanggok dance who is the main resource person, other supporting sources.